Cataract Surgery in Eyes with Congenital Iris–Choroidal Coloboma: Quantitative Assessment of Intraocular Lens Alignment and Optical Quality - Yuxuan Jia; Enjie Li; Zhenyu Wang; Xijin Wu; Xuefei Ding; Qi Zhang; Ting Chen; Peilin Yue; Xudong Song (Journal of Clinical Medicine, 2026)
Background/Objectives: Cataract surgery in eyes with congenital iris–choroidal coloboma is technically challenging, and postoperative intraocular lens (IOL) alignment and objective optical quality remain insufficiently characterized. This study evaluated short-term surgical outcomes, early postoperative IOL alignment, and objective optical quality after phacoemulsification with IOL implantation in eyes with congenital iris–choroidal coloboma and cataract. Methods: This retrospective comparative study included 36 eyes with congenital iris–choroidal coloboma complicated by cataract and 31 eyes with age-related cataract. All eyes underwent phacoemulsification with in-the-bag monofocal IOL implantation. Best-corrected visual acuity (BCVA), intraocular pressure (IOP), early postoperative IOL tilt and decentration, and objective optical quality parameters, including modulation transfer function (MTF) and Strehl ratio (SR), were evaluated 1 month postoperatively. Multivariable linear regression analyses were performed to identify factors associated with postoperative BCVA and IOL tilt in coloboma eyes. Results: BCVA improved significantly after surgery in coloboma eyes (p < 0.001), although postoperative BCVA remained worse than that in age-related cataract eyes after adjustment for age (p < 0.001). IOP showed no statistically significant change in either group. Coloboma eyes exhibited greater IOL tilt and decentration than age-related cataract eyes (7.60 vs. 4.10° and 0.40 vs. 0.14 mm, respectively; age-adjusted p < 0.001 and p = 0.004), with lower MTF and SR (among eyes with evaluable aberrometry, 17 coloboma eyes and 30 age-related cataract eyes, all p < 0.001). Macular and/or optic disc involvement was associated with worse postoperative BCVA and greater postoperative IOL tilt. Conclusions: Phacoemulsification with IOL implantation was associated with short-term visual acuity improvement in eyes with congenital iris–choroidal coloboma. These eyes showed greater early postoperative IOL tilt and decentration than age-related cataract eyes, while the evaluable subgroup showed poorer objective optical quality. Macular and/or optic-disc involvement was associated with worse postoperative BCVA and greater IOL tilt.